KO-INFEKSI ANISAKIDAE DENGAN BERBAGAI PARASIT PADA IKAN KERAPU (Epinephelus sp.) DI TEMPAT PELELANGAN IKAN WERU PACIRAN LAMONGAN - ICE PUTRI HANDAYANI, 061511133060 (2019)
This study aims to determine the existence and identify of Anisakidae larvae and to know the co-infection of Anisakidae with other parasites in groupers at TPI Weru Paciran Lamongan. The grouper samples consisted of 60 individuals consisting of grouper from auction (Epinephelus coioides) and direct catch (Epinephelus fuscoguttatus) by observing larvae stadium III (L3) of Anisakidae in the abdominal cavity, musculus and visceral organs and other parasites on the gills, fins and digestive tract then identified with Semichen Acetic Carmine staining and the prevalence and degree of infection were calculated. The results showed that the larvae stadium III (L3) of Anisakidae found were Anisakis sp. and Terranova sp. The prevalence of Anisakidae at TPI Weru Paciran Lamongan was 77.8% with an infection rate of 5.4 larvae per fish, but did not show co-infection with other parasites. Co-infection occurred in groupers of direct catch between Monogenea and Digenea. Three fish samples were positive for both worm parasites (12.5%).